Impact of ESG Performance on Company Value: Financial Performance as a Mediator in Coal Mining Companies - Aditya Firmansyah; Indra Siswanti (International Journal Labs, 2026)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) performance on firm value with financial performance as a mediating variable in coal mining subsector companies listed on the Indonesia Stock Exchange. This research applies a quantitative approach with a causal research design. The population consists of 16 coal mining subsector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sampling technique employed was purposive sampling, resulting in 8 companies that met the research criteria, with a total of 40 observations. The study uses secondary data obtained from financial statements and sustainability reports. Data analysis methods include descriptive statistics, panel data regression analysis, and the Sobel test, using EViews 12 software. The results indicate that Environmental, Social, and Governance performance partially shows varying effects on firm value. ESG performance significantly influences financial performance. Furthermore, financial performance proxied by Return on Assets (ROA) has a positive and significant effect on firm value. Mediation testing reveals that financial performance mediates the relationship between ESG performance and firm value. These findings indicate that ESG implementation can enhance firm value through improved financial performance.